The depressing nakedness: peran cyberpornography dalam meningkatkan rasa kesepian - Devie Yundianto; Hanifah Khairunnisa (Jurnal Psikologi Tabularasa, 2024)
ABSTRACTThis study aims to discover the influence of cyberpornography on loneliness among students. The study hypothesis is to find out the correlation between dimensions of cyberpornography and differences in the loneliness level within the scope of loneliness in terms of gender and relationship status. The researchers implemented quantitative correlational research as the research method in this study. The researchers used purposive sampling as the sampling technique, with 56 respondents (SD = 1.66) of university students aged 18-27 years who had accessed pornographic content in the last six months. Based on the results, the influence of cyberpornography on loneliness has a significance value of 0.002 and a correlation value of 0.41. In addition, the perceived compulsivity dimension that affects loneliness has a significance value of 0.01 and a correlation value of 0.41. Moreover, the significance value of the access effort dimension is 0.73, and the emotional distress dimension is 0.27, where the p-value > value, so there is no significant effect of these two dimensions on loneliness. Furthermore, on the test based on gender, the significance value is 0.45, and the relationship status is 0.11, where the p-value > alpha means there is no significant difference in loneliness. ABSTRACT Penelitian ini bertujuan untuk mengetahui pengaruh cyberpornography terhadap kesepian di kalangan pelajar. Hipotesis penelitian ini adalah untuk mengetahui korelasi antara dimensi cyberpornography dan perbedaan tingkat kesepian dalam lingkup kesepian ditinjau dari gender dan status hubungan. Para peneliti menerapkan penelitian kuantitatif korelasional sebagai metode penelitian dalam penelitian ini. Peneliti menggunakan purposive sampling sebagai teknik pengambilan sampel, dengan 56 responden (SD = 1,66) mahasiswa berusia 18-27 tahun yang pernah mengakses konten pornografi dalam enam bulan terakhir. Berdasarkan hasil, pengaruh cyberpornography terhadap kesepian mempunyai nilai signifikansi sebesar 0,002 dan nilai korelasi sebesar 0,41. Selain itu, dimensi perceived compulsivity yang mempengaruhi kesepian memiliki nilai signifikansi sebesar 0,01 dan nilai korelasi sebesar 0,41. Sedangkan nilai signifikansi dimensi access effort sebesar 0,73 dan dimensi emotional distress sebesar 0,27 dimana p-value > value maka tidak terdapat pengaruh signifikan kedua dimensi tersebut terhadap kesepian. Selanjutnya pada uji berdasarkan jenis kelamin diperoleh nilai signifikansi sebesar 0,45 dan status hubungan sebesar 0,11 dimana nilai p-value > alpha berarti tidak terdapat perbedaan signifikan terhadap kesepian.